Trelagliptin stimulates osteoblastic differentiation by increasing runt-related transcription factor 2 (RUNX2): a therapeutic implication in osteoporosis. Issue 1 (1st January 2021) - Shao, Haiyu; Wu, Renzheng; Cao, Li; Gu, Haifeng; Chai, Fang
ABSTRACT: Osteoporosis, an aging-associated bone metabolic disease, is affecting millions of people worldwide. The deregulated process of osteoblastic differentiation has been linked with the progression of osteoporosis. Trelagliptin is a long-acting inhibitor of DPP-4 used for the management of type 2 diabetes mellitus. However, it is unknown whether Trelagliptin possesses a beneficial effect in osteoblastic differentiation. Interestingly, we found that treatment with Trelagliptin enhanced differentiation and promoted the mineralization of MC3T3-E1 cells. Firstly, Trelagliptin increased the activity of alkaline phosphatase (ALP) and promoted osteoblastic calcium deposition. Additionally, treatment with Trelagliptin upregulated ALP, osteocalcin (OCN), osteopontin (OPN), and bone morphogenetic protein-2 (BMP-2). Notably, Trelagliptin increased RUNX2, a major regulator of osteoblastic differentiation. Mechanistically, Trelagliptin upregulated the levels of p-AMPKα. Blockage of AMPK with compound C abolished the effects of Trelagliptin in RUNX2 and osteoblastic differentiation, suggesting the involvement of AMPK. Our findings suggest that Trelagliptin might possess a potential for the treatment of osteoporosis. Graphical Abstract: uf0001